Ações estratégicas para a base da pirâmide: estudo de casos em empresas do setor imobiliário da cidade de João Pessoa - Lima, Anderson Santos (2017)
In the last decades, a consumer market known as the Bottom of the Pyramid (BOP), has called the attention for presenting great potential. In Brazil, specifically in the housing sector, through the “My House, My Live” federal programme (PMCMV), many companies have acted towards producing goods which are able to generate social and economic development for society. Nevertheless, in order to penetrate the BoP market, companies must adopt specific strategies, besides counting on proper commercial infrastructure, so that they can overcome difficulties that may be found when assisting that specific market. Therefore, this piece of work aims to characterize the strategic actions adopted in the housing sector in order to assist the population ranked in the BoP market in the city of João Pessoa. Specifically, it aims to describe the key elements of the BoP’s commercial infrastructure in the housing sector, to identify the strategies adopted to attend the housing sector and to outline the role of external agents in the business undertaken. As regards methodology, it was employed the multiple cases studies strategy, using, for that purpose, a construction company, a real state agency, a banking correspondent and three clients. Data was collected from semi-structured interviews, from direct and systematic observations, and from documents. The technique of Content Analysis was used to analyze the data, and in its first stage, the transcription and the organization of the data was done, being followed, in the second stage, by the categorization. In the last stage of the process, treatment of the results, inferences, and interpretation of the data were done. The analysis of the data generated in the process occurred: firstly, individually, and then, the strategic actions that were found were synthesized, in order to verify similarities and differences in the data. The results showed that the commercial infrastructure of the housing sector in the BoP market has similar aspects to the ones found in the main references about the theme. The strategic actions that were found are concerned to encouraging people from the BoP market to buy their property, and the main ones are the following: risk assessment and simplified credit approval, management consulting, use of the internet and the utilization of public policy. In addition, it was observed that the Government, as it is the main external agent, plays an important part in the viability of the housing sector business in the BoP market. It is concluded that, although specif literature addresses several strategies for the BoP market, the ones aimed at involving people and sustainability were not found in the companies which were analyzed. Thus, this paper contributes greatly as it can be considered to be reference work on strategic actions in the housing sector for BoP market.